Welfare Effects of Short-Time Compensation - Helge Braun; Björn Brügemann (Tinbergen Institute, 2017)
We study welfare effects of public short-time compensation (STC) in a model in which firms respond to idiosyncratic profitability shocks by adjusting employment and hours per worker. Introducing STC substantially improves welfare by mitigating distortions caused by public unemployment insurance (UI), but only if firms have access to private insurance. Otherwise firms respond to low profitability by combining layoffs with long hours for remaining workers, rather than by taking up STC. Optimal STC is substantially less generous than UI even when firms have access to private insurance, and equally generous STC is worse than not offering STC at all.
Keywords: J65; 330; Short-Time Compensation; Unemployment Insurance; Welfare